Heuristic Model for Real Estate Development Using Value Management Techniques. Issue 1 (1st March 2015) - Fouda, Ahmed; Shalaby, Ahmed; Farid, Mootaz
Abstract : The real estate development processes involves complex sets of decisions that are related to both technical and financial issues. Some of these decisions could be made simultaneously where the others would be made sequentially. Sequential decisions, especially at early stages of the process, are the most critical for the success of any project. Reliable information at early stages is hard to be found, which makes these decisions rather risky. Budget overruns is also a real risk, which usually appears at last stages of developments especially at tender phase. Developers apply cost saving and/or value engineering / management exercises to reduce the expected cost in order to re-meet the budget again. Value management is preferred since it maintains the same planned quality, provides needed functions and reduces cost. Some of developers succeed where the others are obliged to cancel their developments after wasting a lot of time and money. In order to mitigate some of those risks, enhance development process and optimize the product, developers need to apply a systematic approach in the form of a Heuristic Model as a pro-active tool to assist them performing better. The main objective of this research is to re-utilize the core principle of the value management, which is eliminating unnecessary functions and costs in order to develop this model. Thus, a descriptive analytical approach was applied as a methodology for doing the targeted synchronization and integration between the value management tools and techniques within the real estate development process. The heuristic model proposed a certain order of the development process and selected tools and techniques to achieve the value management philosophy. It is designed to be strategic and flexible in order to guide the developers to create their own model according to their vision and surrounded circumstances.